The role of Islamic education teachers in instilling ukhuwah Islamiyah through tafsir learning - Muchtar, Nicky Estu Putu; Inayah, Karimatul (ATTARBIYAH: Journal of Islamic Culture and Education, 2025)
This study aims to determine the role of Islamic Religious Education teachers in instilling the values of Ukhuwah Islamiyah through thematic tafsir learning of the QS. Al-Hujurat verses 10-13 at MAN 1 Lamongan. These values must be instilled early on, especially amid social divisions, conflicts, and weak student solidarity. Islamic religious education, especially tafsir, is a strategic medium for contextual value formation. This qualitative case study used observation, interviews, and documentation for data collection. The results of this study: First, the PAI teacher acts as a demonstrator, facilitator, class manager, and evaluator. Second is the Cultivation of Ukhuwah Islamiyah Values in Thematic Tafsir Learning QS. Al-Hujurat Verse 10-13 at MAN 1 Lamongan includes the realization of brotherhood between others, peace in the school environment, the formation of tolerant characters, and knowing and understanding each other. Third, challenges arise, such as limited learning time, limited student knowledge about the concept of ukhuwah Islamiyah, the negative influence of social media, and different student backgrounds. This research contributes to a deeper understanding of the practical strategies that can be applied in PAI learning to form an attitude of tolerance and solidarity.